Rewriting history : Peter Carey's fictional biography of Australia - Gaile, Andreas (Costerus ;, 2010)
Peter Carey is one of the most richly awarded and critically acclaimed novelists of the present day. Most of his fictions relate to questions of Australian history and identity. Rewriting History argues that taken together Carey's novels make up a.